ASSISTANCE OF LEGAL PROTECTION FOR THE MARYAM RICE TRADEMARK - Fransisca Kewa Qua; Hari Sutra Disemadi (Universitas Internasional Batam, 2022)
In Law 20 of 2016 concerning Marks and Geographical Indications in Article 1 Paragraph 1 explains that A brand is a sign that is displayed graphically in the form of images, logos, letters, words, and color arrangements in 2 or 3 dimensions by combining these 2 or 3 elements which creates a difference in goods and or services produced by individuals or legal entities in trading activities. Good faith in trademark registration is the beginning of the filing of a trademark registration application in Batam, where each brand and its logo has different characteristics and characteristics from each of the services and goods businesses. In this case, the owner of Nasi Bakar Maryam does not understand and does not know how to do Online Mark Registration. It is important for all Traders to Register their Marks so that they can be legally protected against trademark rights and get legal certainty over the trademarks owned by every trade in Goods and Services. Brands in the world of trade in goods and services have a very important role. For that purpose and from this community service is to register the trademark. The implementation method of this activity has 3 stages, namely making an agreement and explaining to partners the purpose of this activity, collecting the required data, and registering a mark and the result of this activity is that the Nasi Maryam Mark will be registered in Intellectual Property Rights.